Chemical and thermal analysis of troctolite, Hamragarðaheiði, Eyjafjöll, Iceland - Viktor Þór Georgsson 1987- (2016)
This study describes the minerals in a troctolite xenolith from Hamragarðaheiði, Iceland, and its melt inclusions. Studies of xenoliths from deep inside the crust provide an interesting picture on crustal structure and on the mantle-crust interaction (Gurenko & Sobolev, 2006). Previous studies and available literature on Icelandic crustal xenoliths are rare, this thesis provides additional knowledge to that list and furthers the understanding on mantle-crust relations beneath Iceland. Olivine in the troctolite have Fo61.6-78.2 showing high MgO concentration of 30.45-41.32 wt%, and FeO ranging from 20.16-33.83 wt%. Plagioclase are mostly labradorite and bytownite with An41.75-87.37. Al2O3 was measured in the range of 26.64-36.15 wt.% and CaO had a wide range of 9.39-18.77 wt.%. The pyroxene has high MgO concentration in the range of 13.83-16.97 wt.% giving them a Mg# in the range of 74.3-80.2. Compositions in the pyroxene are Wo39.77-45.89En40.98-48.39Fs11.48-14.55, which makes them cluster at the border between augite and diopside. The melt inclusions, corrected for post entrapment modification, have a Mg# ranging from 33.86-51.69, they have Al2O3 concentration in the range of 11.36-18.75 wt.%, the FeO concentration ranges from 5.54-18.29 wt.%, MgO has the range of 3.03-8.95 wt.%, and CaO concentration ranges from 10.04-15.21. Comparison between the chemical compositions in the troctolite to chemical compositions in the host rock and from the eruption at Fimmvörðuháls 2010 show much similarities. Thermal calculations were carried out on olivine hosted and plagioclase hosted melt inclusions in the troctolite and they show an average temperature of crystallization at 1147 ± 45°C. Rannsóknin sem hér verður fjallað um lýsir steindum og glerinnlyksum úr troktólít framandstein sem fannst á Hamragarðaheiði, Íslandi. Rannsóknir á framandsteinum sem eru frá miklu dýpi í skorpunni geta veitt áhugaverða mynd af byggingu skorpunnar og samskiptum möttuls við skorpuna (Gurenko & Sobolev, 2006). Fyrri rannsóknir og ...